Front Cover: Enzyme Engineering Enables Inversion of Substrate Stereopreference of the Halogenase WelO5* (ChemCatChem 24/2022). Issue 24 (5th December 2022) - Voss, Moritz; Hüppi, Sean; Schaub, Daniela; Hayashi, Takahiro; Ligibel, Mathieu; Sager, Emine; Schroer, Kirsten; Snajdrova, Radka; Buller, Rebecca
Abstract : The Front Cover depicts the opportunity to selectively chlorinate distinct stereoisomers of a bioactive molecule through the choice between tailored stereo‐complementary halogenase variants. In their Research Article, R. Buller and co‐workers describe the inversion of halogenase WelO5*'s substrate stereopreference through enzyme engineering. The resulting two halogenase variants enable the resolution of four stereoisomers of a martinelline‐derived fragment by chlorination. In addition, the elucidation of protein crystal structures informs about factors governing substrate specificity. More information can be found in the Research Article by R. Buller and co‐workers .